Study of risk factors, prognostic value of some biochemical, hematological and oxidative stress markers and evaluation of the effect of Proso millet on osteoporosis in postmenopausal women from Guemar (El Oued, Algeria) region - HADDIG Nour El-Houda; ZERZOUR Aicha (Université of Eloued جامعة الشهيد حمه لخضر, 2020)
The main purpose of this work was to assess some socioeconomic and clinic risk factors of osteoporosis disease, to analysis some biological and oxidative stress markers to predict and diagnose this disease and to evaluate the effects of Proso millet aqueous extract against osteoporosis in postmenopausal women of Guemar El-Oued region. Our socioeconomic and clinic risk factors study was conducted on 241 postmenopausal volunteers divided into 100 healthy women and 141 women patients with osteoporosis. For biological analysis of osteoporosis we have chosen 16 healthy women as control and 16 menopausal women have osteoporosis, we used this second group for Proso millet aqueous extract treatment during four weeks. The results of risk factors study illustrate the high relationship between some clinical factors such as hormonal alternatives, menstrual perturbations and vitamin D deficiency before menopause and thyroid problems are shown to be significant risk factors, but bone problems before menopause and family history are the most dangerous risk factors (OR = 65.646; OR= 41.152) respectively, for osteoporosis in postmenopausal women. While, milk, fish diet, legumes, fresh vegetables and fruits, sunshine exposure, long distance walks and menopause after 50 years old are protective factors against this disease. Our results of biological study demonstrate a significant variations (P<0.05) in biochemical parameters, hematological markers and oxidative stress markers which some of them represented an important significant specificity (P<0.05) such as MDA in leukocyte (AUC=70.7%), in serum (AUC=99.6%) and sedimentation rate in both 1st (AUC=69.9%) and 2nd hour (AUC=60.2%). About phytotherapeutic study, the results of the qualitative and quantitative analysis revealed that the aqueous extract of the plant is rich in alkaloids, tannins, flavonoids, saponins, reducing sugars and terpenoids, with a considerable levels of phenols and flavonoids. The results show also that the plant extract significantly reverse (P<0.05) the change of calcium, GSH, SOD and ORAC levels induced by osteoporosis which represent the efficiency of the plant in reducing its severity. In conclusion, several clinical factors contributed to the evolution of the osteoporosis in postmenopausal women in Guemar El-Oued region. MDA level in leukocyte and in serum and the sedimentation rate in both 1st and 2nd hour represent very important predictive factors for the studied disease. The phytotherapy have beneficial effects on the oxidative stress and calcium status in case of osteoporosis in postmenopausal women.
Applied Biochemistry
Keywords: Osteoporosis; Post-menopause; Risk factors; Oxidative stress; Calcium; Proso millet; الدرع; هشاشة العظام